The Fragile Wisdom: an evolutionary view on women's biology and health - Grazyna Jasienska (Harvard University Press, 2013)
Many women put a lot of effort into following what they are told is a healthy lifestyle. They do not smoke, eliminate fatty foods from their diets, cut back on sweets, take stairs instead of elevators, and walk to work. When they get sick with breast cancer, heart disease, or osteoporosis, they often blame themselves and ask, â€œWhat did I do wrong?â€ We hear so much about how different diseases can be prevented by a â€œhealthyâ€ way of living that when we become ill we often believe that it happened because we somehow failed in our attempts to follow all the recommendations. I hope that this book will show that people should not blame themselves for becoming ill. Of course, there are behaviors that without a doubt are bad for us. Smoking increases the risk of many diseases, and not smoking or giving it up results, for an average person, in much better health and an extended life. What other lifestyle decisions would have a similar effect? Most people would say exercise and eating right. That is true, but in fact we do not know for sure what exercise and eating right really mean when it comes to providing concrete advice to a specifi c individual. One of the themes of this book is an attempt to understand why specifi c recommendations about physical activity and diet are so diffi cult to formulate. Some researchers think that the key to understanding what is good for us when it comes to a recommended lifestyle is greater knowledge about the physical activity and diet of our ancestors during evolutionary times (i.e., more than 10,000 years ago). This is clearly a good starting point, but the question remains as to whether what was good for our ancestors is still appropriate for us. We cannot replicate their past life, but if we can pick just some aspects of an evolutionary lifestyle and incorporate them into our lives, would that be enough to prevent diseases?